Preparing undergraduate nurses for the workforce in the context of patient safety through innovative simulation : final report. - Reid-Searl, Kerry; Levett-Jones, Tracy; Andersen, Patrea; Guinea, Stephen; Dwyer, Trudy; Heaton, Leeanne; Flenady, Tracy; Applegarth, Judy (Australia. Dept of Education and Training (DET), 2019)
This collaborative project responds to the growing demands for nursing graduates to be cognisant and capable of contributing to patient safety in practice. With reference to patient safety reports, coroners' reports, contemporary literature and government priorities, this project addresses the specific knowledge, skills and attributes industry expect of nursing students and graduate nurses regarding patient safety. Central to this project is the in corporation of the National Safety Quality Health Service (NSQHS) Standards. This project delivers a Patient Safety Competency Framework for Nursing Students and an innovative, new and multimodal approach to simulation called Tag Team Patient Safety Simulation (TTPSS). The TTPSS is intended to enhance graduates' employability skills by facilitating their capacity to practice safely. Further more, it enables educators to deliver patient safety simulation scenarios to large or small cohorts of students in various contexts and without the need for highly technical equipment. The TTPSS approach is designed to enable simulation to occur 'without walls' as it is not confined to a traditional simulation laboratory space. The Tag Team approach to simulation could potentially occur in any environment. [Executive summary, ed]